2013
DOI: 10.1002/chin.201302057
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Facile Synthesis of Bromoallenes via N‐Bromosuccinimide/CH3SCH3 for the Bromination of Propargyl Alcohols.

Abstract: The reagent combination allows a regioselective preparation of the target compounds (10 examples).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…904 Du et al reported a convenient pathway for the preparation of bromoallenes from propargyl alcohols by the combination of NBS and dimethyl sulfide. 905 Bromoallenes were obtained with high regioselectivity (Scheme 281). The substituents located at the para or meta position of the aromatic ring do not have a significant influence on the bromination, while the ortho position of the aromatic ring affects the bromination reaction, causing a lower yield of the product.…”
Section: Aromatic Bromination Using Nbsmentioning
confidence: 99%
“…904 Du et al reported a convenient pathway for the preparation of bromoallenes from propargyl alcohols by the combination of NBS and dimethyl sulfide. 905 Bromoallenes were obtained with high regioselectivity (Scheme 281). The substituents located at the para or meta position of the aromatic ring do not have a significant influence on the bromination, while the ortho position of the aromatic ring affects the bromination reaction, causing a lower yield of the product.…”
Section: Aromatic Bromination Using Nbsmentioning
confidence: 99%